BASIC TILLAGE BY MODERNIZED CHISEL TOOLS - I. B. Borisenko; A. E. Novikov; M. A. Sadovnikov (Сельскохозяйственные машины и технологии, 2017)
The choice of the method of basic cultivation must be differentiated, considering zonal soil and climatic conditions and local peculiarities of the fields. Chisel tillage refers to soil conservation technologies, and chisel tools provide low-power and, if it is necessary, differential loosened soil, the accumulation, preservation and rational use of soil moisture that is relevant in the arid climate. The authors designed the combined chisel working implements RANCHO, ROPA, plow-cultivator. The traction resistances of the working tools were studied strain-gauge method. The unified equation of traction resistance chisel working was developed. The resistance of tine, chisel, additional equipment on the tine and the dynamics of the chiseling were introduced. The resistance of the chisel was determind by pressure from the soil on its surface. If the speed of machine-tractor aggregate will increase from 1 to 3 m/s then traction resistance of the working implements ROPA will rise by 26-29 percent, plow-cultivator - by 21-23 and classic mould-board plough - by 35 percent due to more significant influence of the dynamic component during moving mould-board plough in the undisturbed soil. The plowing work by the plow-cultivator in comparison with mould-board plough provides more depth of soil loosening (0.38 m when 0.15 m real tillage and 0.2 m in control variant) at comparable energy consumption.